Enfermedad de Chagas en Argentina: herramientas para que los escolares vigilen y determinen la presencia de factores de riesgo en sus viviendas - Crocco, Liliana Beatriz (2005)
The objective of this paper was to validate tools for schoolchildren to help control Chagas disease vectors in their own homes. Two types of tables were produced, one reporting on the presence of risk factors in residences and the other to record the presence of triatomines. The materials were tested in the field by 100 students from an endemic area in Argentina and validated by technical personnel. The results obtained by students concerning the percentage of households with risk factors and vector-positive residences were similar to those obtained by the technical personnel. This information allowed teachers to classify the risk levels in the residences as at ?high-risk?, ?risk?, or ?no risk?. The information provides an important aid for health workers, and it is therefore recommended to include this educational strategy in the surveillance phase of the Chagas disease control program.